Isolation of vancomycin-resistant Staphylococcus aureus in a patient with burn injury. Issue 1 (January 2016) - Ranjbary, Ali Ghorbani
Abstract : Most common nosocomial and community-acquired infections worldwide are caused by Staphylococcus aureus . Vancomycin is still preferred for the treatment of methicillin-resistant S. aureus infections. In November 2013, a 50-year-old man presented to a hospital in Shiraz with burn injuries as a result of electrical exposure. The patient had no underlying disease or abnormality. While he was at home, the electrical exposure caused a fire and injured him. The wounds were closed with gauze. Blood and wound samples were obtained for culture each day. On the third day after admission, the wound was infected and S. aureus was isolated. Finally, we performed PCR for detection of nuc, mecA, vanA, and vanB genes using a specific primer. In conclusion, we suggest physicians to consider vancomycin-resistant S. aureus as a probable cause of infection in hospitalized patients, especially in wards with high drug-resistance rates, such as burns units.